2016
DOI: 10.1055/s-0042-114774
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal endoscopic submucosal dissection: a systematic review and meta-analysis

Abstract: Background and study aims: Endoscopic submucosal dissection (ESD) is an advanced endoscopic technique that allows en-bloc resection of gastrointestinal tumor. We systematically review the medical literature in order to evaluate the safety and efficacy of colorectal ESD. Patients and methods: We performed a comprehensive literature search of MEDLINE, EMBASE, Ovid, CINAHL, and Cochrane for studies reporting on the clinical efficacy and safety profile of colorectal ESD. Results: Included in this study were 13833 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
82
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 75 publications
10
82
0
2
Order By: Relevance
“…Three recent studies on ESD for UC‐associated dysplasia have reported en bloc resection rates of 80–100% and R0 resection rates of 70–76% . These results are comparable with the outcomes summarized in the systematic reviews of ESD for almost exclusively sporadic CRN ( en bloc resection rates of 89–92% and R0 resection rates of 76–83%) . However, the R0 resection rate for ESD of UC‐associated dysplasia seems relatively lower than the pooled R0 resection rate of 85.6% reported previously in an Asian subgroup .…”
Section: Discussionsupporting
confidence: 71%
“…Three recent studies on ESD for UC‐associated dysplasia have reported en bloc resection rates of 80–100% and R0 resection rates of 70–76% . These results are comparable with the outcomes summarized in the systematic reviews of ESD for almost exclusively sporadic CRN ( en bloc resection rates of 89–92% and R0 resection rates of 76–83%) . However, the R0 resection rate for ESD of UC‐associated dysplasia seems relatively lower than the pooled R0 resection rate of 85.6% reported previously in an Asian subgroup .…”
Section: Discussionsupporting
confidence: 71%
“…This means that it takes a longer time for Western endoscopists to obtain sufficient experience in gastric ESD, making it difficult to step up to colorectal ESD. In fact, the en bloc and R0 resection rates in Western countries were reported to be lower than in Japan; and many reports were limited to treatments of the rectum or distal colon . The aforementioned studies, particularly those from Japan, were retrospective analyses of the experience of endoscopists who have stepped up to colorectal ESD after gaining sufficient experience in gastric ESD .…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all of these results are obtained from large series from expert centers in Asia, primarily Japan 9. The adoption of ESD in western practice has been very limited because of its technical difficulty, steep learning curve and the difference in training opportunities compared to Japan because of the relative scarcity of early gastric and esophageal cancer 1214.…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter study found that, regardless of the technique employed, piecemeal resection was the most important risk factor for recurrence; also, a meta-analysis of risk factors for local recurrence found that piecemeal resection was the only independent risk factor for recurrence 30,31. Akintoye et al included several thousands of cases of ESD in a meta-analysis and found a pooled recurrence rate of only 1% 9. Other meta-analyses have consistently demonstrated rates of local recurrence after ESD of 0.7%–1.2%, compared to 10.4%–12.7% after EMR 6,8,22,23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation